Innovation in Arabic Language Learning Methods in Elementary Schools: Enhancing Students' Interest and Abilities - Amal, Ihsanul; Choir, Jihan Alhanin (Journal of Practice Learning and Educational Development, 2025)
Innovation in methods of learning Arabic in primary schools plays a crucial role in improving students' interests and abilities. This article explores a range of innovative approaches that can be applied in Arabic language teaching, including the use of digital technology, game-based approaches, and communicative methods. The main focus of the study is to analyze the impact of these methods on the motivation of students and their learning outcomes. By applying a qualitative approach, the study collects data through classroom observations, interviews with teachers, and student surveys. The findings show that innovative methods significantly improve student engagement and learning effectiveness. Digital technology provides exciting and interactive access to material, educational games add elements of fun and motivation, communicative methods enhance practical skills, and contextual teaching makes language more relevant in everyday life. This article provides practical recommendations for implementing these methods in the classroom, as well as emphasizing the importance of support from schools and parents to optimal results.